ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN HIGHER EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
The present conceptual paper explores on the Role of Artificial Intelligence (AI) in Higher Education. Artificial intelligence (AI) is gaining significance in all the sectors of the economy and hence in higher education too. From last few years, this concept of “Artificial Intelligence (AI) in Higher Education has experienced significant developments. This study attempted to discuss the role and concept of Artificial Intelligence (AI) can be applied in teaching and learning in higher education and importance of using AI in Higher Education. AI is a study of how human brain think, learn, decide, and work, when it tries to solve problems. The aim of AI is to improve computer functions which are related to human knowledge, for example, reasoning, learning, and problem-solving. AI gives opportunities to higher education services to become easily accessible at an extraordinary speed, not only inside the class but also outside the classroom. This report attempts to figure out the how AI can become an integral part of universities and tried to access it’s immediate and future implications on different areas of higher education.The present paper deals with the study Role of Artificial Intelligence (AI) in Higher Education with prime objectives are (i) To understand the concept of Artificial Intelligence (AI). (ii) To analyses the role of technologies related Artificial Intelligence (AI) in Higher Education. (iii) To discuss the importance of Artificial Intelligence (AI) in Higher Education.The methodology of the research is a different type involving an interpretative, conversation, observation, and study secondary sources, like books, articles, journals, thesis, university news, expert opinion, and websites, etc.